Photophysical properties of blue-emitting silicon nanoparticles - Llansola Portolés, Manuel Jose (2009)
Silicon nanoparticles with strong blue photoluminescence were synthesized by electrochemical etching of silicon wafers and ultrasonically removed under N 2 atmosphere in organic solvents to produce colloids. Thermal treatment leads to the formation of colloidal Si particles of 3 ± 1 nm diameter, which upon excitation with 340-380 nm light exhibited room temperature luminescence in the range from 400 to 500 nm. The emission and the one- and two-photon excitation spectra of the particles are not sensitive to surface functionalization with methyl 2-methylprop-2-enoate. However, the derivatized particles show higher emission quantum yields in air-saturated suspensions (44%) than the underivatized particles (27%), as well as higher stability of its dispersions. FTIR and XPS spectra indicate a significant surface oxidation of the particles. The Si:O:C ratio at the surface of the derivatized particles estimated from XPS is Si 3O 6(C 5O 2H y) 1, with y =7-8. Vibronic spacing is observed in both the emission and excitation spectra. The information obtained from one-photon excitation experiments (emission and excitation spectra, photoluminescence quantum yields, luminescence decay lifetimes, and anisotropy correlation lifetimes), as well as from two-photon excitation fluorescence correlation spectroscopy (brightness and diffusion coefficients) and TEM, indicate that the blue-emitting particles are monodisperse and ball-shaped. Particle size clearly determines the emission and excitation spectral region, as expected from quantum confinement, but the presence and extent of Si-O species on the silicon networks seem crucial for determining the spectrum features and intensity of emission. The nanoparticles could hold great potential as quantum dots for applications as luminescence sensors in biology and environmental science. © 2009 American Chemical Society.